Analisa Kebisingan di Ruas Jalan Arteri Kota Surabaya Serta Korelasinya Dengan Nilai Volume Lalu Lintas - Zetta Rasullia Kamandang; Hendrata Wibisana; Cintantya Budi Casita (Jurnal Aplikasi Teknik Sipil, 2020)
Sound pollution is a negative impact that occurs from the accumulation of the number of vehicles on a road where vehicles with each other crammed together to be able to drive without slowing down. This study aims to map the value of noise caused by motorized vehicles on arterial roads in the West Surabaya region. As for the method used to do the mapping is the application of geographic information systems based on primary data obtained in the form of vehicle volume and noise values measured by the tool sound level meter, analysis is done using multiple regression and correlation analysis with distribution t. The results obtained from this study are mathematical models of noise on various types of vehicles as well as a correlation model of noise with a degree of saturation. From this study it can be concluded that there is a positive correlation of noise with the degree of saturation where the mathematical model obtained Noise = 137.45 * DS + 34.76, for each increase in the degree of saturation will increase the noise value, in other words the degree of saturation is directly proportional to noise